Die postmigrantische Gesellschaft: Ein Versprechen der pluralen Demokratie - Foroutan, Naika (transcript, 2021)
The empowerment of right-wing movements in immigration countries creates increased tension in the society that is reflected in polarization and growing ambivalences: On the one side, these societies are based on values of plural democracy, which aims at equality for all citizens; on the other side, these trends that question this promise of equality enjoy growing popularity. Naika Foroutan shows that the line of conflict only seems to run along the positioning for or against migration. This is less about migration per se than about the processes of negotiation that occur after migration has become a political reality and hegemonic positions have been questioned.